The right to health, health systems development and public health policy challenges in Chad - Azétsop, Jacquineau (Philos Ethics Humanit Med, 2015)
BACKGROUND: There is increasing consensus that the right to health can provide ethical, policy and practical groundings for health systems development. The goals of the right to health are congruent with those of health systems development, which are about strengthening health promotion organizations and actions so as to improve public health. The poor shape and performance of health systems in Chad question the extent of realization of the right to health. Due to its comprehensiveness and inclusiveness, the right to health has the potential of being an organizational and a normative backbone for public health policy and practice. It can then be understood and studied as an integral component of health systems development. METHOD: This paper uses a secondary data analysis of existing documents by the Ministry of Public Health, Institut National de la Statistique, des Etudes Economiques et Démographiques (INSEED), the Ministry of Economy and Agence Française de Cooperation to analyze critically the shape and performance of health systems in Chad based on key concepts and components of the right to health contained in article 12 of the International Covenant on Economic, Social and Cultural Rights, and on General Comment 14. RESULTS: The non-realization of the right to health, even in a consistently progressive manner, raises concerns about the political commitment of state officials to public health, about the justice of social institutions in ensuring social well-being and about individual and public values that shape decision-making processes. Social justice, democratic rule, transparency, accountability and subsidiarity are important groundings for ensuring community participation in public affairs and for monitoring the performance of public institutions. CONCLUSION: The normative ideals of health systems development are essentially democratic in nature and are rooted in human rights and in ethical principles of human dignity, equality, non-discrimination and social justice. These ideals are grounded in an integrated vision of society as a place for multi-level interactions, where government plays its role by equitably providing institutions and services that ensure people’s welfare. Inter-sectoral collaboration, which calls for a conceptual shift in health and public policy, can be instrumental in improving health systems through concerted efforts of various governmental institutions and civil society.